Cytotoxic T cells in AIDS colonic cryptosporidiosis. Issue 4 (1st April 2001) - Reijasse, D; de Serre, N Patey-Mariaud; Canioni, D; Huerre, M; Haddad, E; Leborgne, M; Blanche, S; Brousse, N
Abstract : Background/Aims —It is not known how enteric cryptosporidiosis induces severe intestinal impairment despite minimal invasion by the parasite. The aim of this study was to analyse the histological features and locally implicated immune cells in colonic biopsies of AIDS related cryptosporidiosis. Patients/Methods —Colonic biopsies from patients with AIDS related cryptosporidiosis (n = 10, group I), patients with AIDS but without intestinal infection (n = 9, group II), and human seronegative controls (n = 9, group III) were studied. Using immunohistochemistry the infiltrating mononuclear cells were analysed in both the epithelium and lamina propria for the expression of CD3, CD8, TiA1, granzyme B, and CD68 and for glandular expression of human major histocompatibility complex DR antigen (HLA-DR). Results —Severe histological changes, resulting in abundant crypt epithelial apoptosis and inflammatory infiltrate in the lamina propria, were seen in all biopsies from group I. A significant increase of CD8+, TiA1+, and granzyme B+ T cells in the lamina propria and HLA-DR glandular expression was noted in group I compared with groups II and III. However, the number of intraepithelial lymphocytes, lamina propria CD3+ T cells, and macrophages was not significantly increased in cryptosporidiosis specimens compared with controls. Conclusion —Epithelial apoptosis mediated by granzyme B+ cytotoxic host T cells might play a major role in the development of colonic lesions in AIDS related cryptosporidiosis.